Boards as a Source of Inertia: Examining the Internal Challenges and Dynamics of Boards of Directors in Times of Environmental Discontinuities - Hoppmann, Joern; Naegele, Florian; Girod, Bastien (Academy of Management Journal, 2019)
The literature on corporate governance indicates that, by engaging in strategy-related activities, boards of directors can help firms adapt to environmental discontinuities. So far, however, studies shed limited light on board-internal challenges and dynamics in such difficult times, thus providing few insights into the conditions under which boards may contribute to organizational inertia. We use a comparative case study of 10 major Swiss electric utility companies during the energy transition to show in detail how environmental and strategic change impair boards’ ability to judge strategic issues, and how boards use self-evaluation and self-reconfiguration to renew this ability. Moreover, we offer original insights into the board-internal antecedents of board renewal, and show that environmental discontinuities pose a dilemma for boards, since self-evaluation and self-reconfiguration are critical for preventing organizational inertia yet may run counter to board members’ self-interest. By showing that board members, like managers, experience conflicts of interest that can harm firm performance, our study contributes to agency theory and an emerging micro-perspective on boards. Moreover, by highlighting boards as a source of organizational inertia, our study challenges existing findings in the field of strategic management and makes several more specific contributions to important debates in the corporate governance literature.